Semiotic Analysis Roland Barthes of The Movie “Hachiko: A Dog’s Tale” - Firlianty, Lie Fika (Titik Imaji, 2024)
Movies serve not only as entertainment but also as a means of communication to conveying moral, social, and religious values. There are several films inspired by true stories, including interactions between humans and animals that are compelling to narrate. One such film is "Hachiko: A Dog’s Tale," which tells the story of a dog's loyalty to its owner. The presence of an animal so close to humans and the story built from their interaction is believed to convey a message beyond the everyday relationship between a pet and its owner. The true story of Hachiko, who waited at the station every day even though his owner had passed away, intrigued researchers to understand the deeper position of each subject in conveying moral messages in this tale. Analysis was conducted using Roland Barthes' Semiotics approach to explore the messages conveyed through the interaction between humans and animals. The analysis process focused on signs (signifiers) and meanings (signified) in several scenes from the film. This research revealed the emotional closeness and loyalty of Hachiko to his owner, evident in the signs portrayed in various moments throughout the film. The findings suggest that this film not only portrays the story of a dog's loyalty but also conveys a moral message about the importance of commitment and loyalty in human relationships within society.